Actividades de germoplama de frijol. Unidad de Biotecnología - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1986)
In 1985, the activities of the Biotechnology Research Unit (CIAT) involved research in cell and tissue culture for clonal propagation and for the generation of useful variability. These activities included work carried out at CIAT and at collaborating institutions abroad. Work at CIAT concentrated on research to develop tissue culture applications with CIAT crops, including beans. (CIAT)